Cleavage and Formation of Molecular Dinitrogen in a Single System Assisted by Molybdenum Complexes Bearing Ferrocenyldiphosphine1. (11th September 2014) - Miyazaki, Takamasa; Tanaka, Hiromasa; Tanabe, Yoshiaki; Yuki, Masahiro; Nakajima, Kazunari; Yoshizawa, Kazunari; Nishibayashi, Yoshiaki
Abstract The NN bond of molecular dinitrogen bridging two molybdenum atoms in the pentamethylcyclopentadienyl molybdenum complexes that bear ferrocenyldiphosphine as an auxiliary ligand is homolytically cleaved under visible light irradiation at room temperature to afford two molar molybdenum nitride complexes. Conversely, the bridging molecular dinitrogen is reformed by the oxidation of the molybdenum nitride complex at room temperature. This result provides a successful example of the cleavage and formation of molecular dinitrogen induced by a pair of two different external stimuli using a single system assisted by molybdenum complexes bearing ferrocenyldiphosphine under ambient conditions.